Fast, cheap and sensitive: Homogenizer-based RNA extraction free method for SARS-CoV-2 detection by RT-qPCR - Ramírez-Córdova, Cristina; Morales-Jadán, Diana; Alarcón-Salem, Sofía; Sarmiento-Alvarado, Alisson; Proaño, María Belén; Camposano, Isabel; Sarmiento-Alvarado, Berenice; Bravo-Castro, Mishell; Hidalgo-Jiménez, Jean Franco; Coello, Dayana; Rodríguez, Ángel S.; Viteri-Dávila, Carolina; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background The SARS-CoV-2 gold standard detection method is an RT-qPCR with a previous step of viral RNA extraction from the patient sample either by using commercial automatized or manual extraction kits. This RNA extraction step is expensive and time demanding. Objective The aim of our study was to evaluate the clinical performance of a simple SARS-CoV-2 detection protocol based on a fast and intense sample homogenization followed by direct RT-qPCR. Results 388 nasopharyngeal swabs were analyzed in this study. 222 of them tested positive for SARS-CoV-2 by the gold standard RNA extraction and RT-qPCR method, while 166 tested negative. 197 of those 222 positive samples were also positive for the homogenization protocol, yielding a sensitivity of 88.74% (95% IC; 83.83 – 92.58). 166 of those negative samples were also negative for the homogenization protocol, so the specificity obtained was 97% (95% IC; 93.11 – 99.01). For Ct values below 30, meaning a viral load of 103 copies/uL, only 4 SARS-CoV-2 positive samples failed for the RNA extraction free method; for that limit of detection, the homogenizer-based method had a sensitivity of 97.92% (95% CI; 96.01 – 99.83). Conclusions Our results show that this fast and cheap homogenization method for the SARS-CoV-2 detection by RT-qPCR is a reliable alternative of high sensitivity for potentially infectious SARS-CoV-2 positive patients. This RNA extraction free protocol would help to reduce diagnosis time and cost, and to overcome the RNA extraction kits shortage experienced during COVID-19 pandemic.